THE UNITED NATIONS CHARTER AND THE RESPONSIBILITY TO PROTECT: INTERROGATING THE HUMANITARIAN CRISIS IN SYRIA - ANTHONY IMEH UMOH; BARINAADAA NWINKOL (International Studies Journal)
The Syrian crisis which began in 2011 has left in its trail series of humanitarian catastrophe that has begged for solution. The crisis has decimated the country’s population since it started in 2011, provoking serious humanitarian crisis. The United Nations Charter gives responsibility to international community to use appropriate diplomatic and other peaceful measure in accordance with Chapter VI and VIII of the Charter to help protect populations from genocide, war crimes, ethnic cleansing and crime against humanity. In the same vein, the responsibility to protect populations from genocide and other gross forms of human rights abuse emerged in 2005 as an important global principle during the UN World Summit Outcome Document. This article examines the UN Charter and the responsibility to protect principle and x-rayed how it has impacted the Syrian crisis vis-à-vis humanitarian crisis. The paper questioned why the case of Syria is different despite having been implemented in Libya before. The paper concludes that the case of Syria is different because she is backed by a superpower, Russia and the fact that politics thrive on interest, the other superpower stand to gain nothing from Syria.